Stuck at the start: young workers' experiences of pay and progression (London, 2018)
"Young people are getting a raw deal at work. Low pay, few opportunities to progress and a feeling that nothing will change often dominate their working lives. But this is through no fault of their own. Many of the barriers facing young workers are structural and outside of their control.This report identifies five issues that young workers face in getting ahead at work and makes recommendations to help."